Athlete as a profession (Journal of Parents and Teachers, 2024)
The following article is a kind of interview, in which six individuals who have dedicated their lives to sports answer six questions related to their life. These questions focus on their beginnings, dedication, the significance of sports for them, and the impact it has on education. In general, there is a tremendous importance in their lives revolving around sports and its teachings.